2018
DOI: 10.21512/humaniora.v9i2.4562
|View full text |Cite
|
Sign up to set email alerts
|

Development of Student Worksheet on Materials Economy Based Problem Solving

Abstract: This research aimed to determine the validity, practicalities, and effectiveness development of student worksheet on materials economy based on problem solving for Junior High School students Yayasan Pendidikan Islam (YPI) Tunas Bangsa Palembang. This research was developed consisting of four stages; define, design, develop, and disseminate known as 4D development models. The instruments were the validation sheet, questionnaire, observation sheet, and test sheet. The research and development data consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
2
1
0
2
Order By: Relevance
“…In the aspect of content, attention is paid to the suitability of the material with the desired competence. This is in line with the opinion which states that the development of student worksheets must consider the suitability of the material with the competencies to be achieved (Muslim et al, 2020;Pratita et al, 2018). This E-Student Worksheet also considers the accuracy of the facts and theory of the material developed.…”
Section: Discussionsupporting
confidence: 74%
“…In the aspect of content, attention is paid to the suitability of the material with the desired competence. This is in line with the opinion which states that the development of student worksheets must consider the suitability of the material with the competencies to be achieved (Muslim et al, 2020;Pratita et al, 2018). This E-Student Worksheet also considers the accuracy of the facts and theory of the material developed.…”
Section: Discussionsupporting
confidence: 74%
“…The data of this research are in line with the results of the research by [10] with the title research Development of Student Worksheet on Materials Economy Based Problem Solving said that Based on the results of this research, it concludes that the student developed worksheet with problembased instruction is valid, practical, and effective, so it is very well used by the teacher as a supplement in teaching to complement the teaching materials in the learning process. Then [7] with the research Development of Problem Solving-Oriented Worksheet of Physics Learning In Senior High School said that The results showed that the average increase in the learning outcomes of the learners was equal to 79.44 with a difference in the scores of learning outcomes where tcount = 32.806 > ttable = 1.734, with a significance level of 0.000.…”
Section: Figure 1 Validation Diagram Of Expert Content / Materials Phsupporting
confidence: 80%
“…LKS memberikan struktur dan panduan bagi siswa, termasuk instruksi pembelajaran, indikator, informasi pendukung, langkah-langkah kerja, dan penilaian (Iswatiningsih et al, 2021). Namun, penting untuk memastikan bahwa LKS yang digunakan memenuhi semua elemen yang diperlukan untuk menjaga minat dan keterlibatan siswa (Iswatiningsih et al, 2021;Pratita et al, 2018). LKS berbasis model pembelajaran POE yang dikembangkan dalam penelitian ini telah dinyatakan valid sehingga dapat dinyatakan memenuhi elemen-elemen penting untuk menjaga minat dan keterlibatan siswa dalam pembelajaran seperti diuraikan hasil-hasil penelitian terdahulu.…”
Section: Gambar 2 Keterlaksanaan Pembelajaranunclassified
“…Penggunaan LKS memungkinkan pembelajaran berbasis penyelidikan seperti yang diterapkan dalam penelitian ini dapat mendorong pemecahan masalah, keterampilan kognitif, dan pemahaman konsep (Aka et al, 2021). LKS dalam penelitian ini lebih lanjut sekalan dengan pendapat bahwa LKS berbasis penyelidikan memfasilitasi pembelajaran aktif, di mana siswa mengemukakan pendapat, bertanya, dan terlibat dalam diskusi kelompok (Aulianingsih et al, 2020;Pratita et al, 2018).…”
Section: Gambar 2 Keterlaksanaan Pembelajaranunclassified